Hi
I know this is a bit basic but how do I re-arrange this so that I have a formula that reads "v = ......"?
.45v = v - c- s - a -vr - v((0.1 - (d+r)) - p
It's a while since I've done any algebra. Thanks in advance
Mark G
move all terms with the factor v to the same side of the equation ...
$\displaystyle .45v - v + vr + v[0.1 - (d+r)] = -c - s - a - p$.45v = v - c- s - a -vr - v((0.1 - (d+r)) - p
factor out v from each term ...
$\displaystyle v(.45 - 1 + r + [0.1 - (d+r)]) = -(c+s+a+p)$
divide ...
$\displaystyle v = -\frac{c+s+a+p}{r + [0.1 - (d+r)] - .55}$